Resistensi Tokoh-tokoh Perempuan Terhadap Patriarki dalam Novel Garis Perempuan karya Sanie B Kuncoro - Delmarrich Bilga Ayu Permatasari (Jentera: Jurnal Kajian Sastra, 2017)
This article aims to reveal the meaning of the resistance movement of female characters in the novel Garis Perempuan by Sanie B. Kuncoro. Ranting, Gendhing, Tawangsri and Zhang Mey are adult women who live in the midst of modernity, but have cultural roots that can not be separated from the thick patriarchal law. Raised with different cultural backgrounds, the four characters have their own way of making efforts to reach welfare, personal freedom, and social justice  that are embodied as a whole in the effort to meaning the virginity. By using the concept of criticsm of feminies literature, it can be concluded that virginity is a liquid thing that women use as a form of appreciation of their bodies so that by apreciate its virginity a woman has power over her body ownership which in culture and patriarchy law women's authority over the possessions of their bodies is often ignored.